The Linear 2- and 4-Arboricity of Complete Bipartite Graph Km, n. (30th December 2013) - Zuo, Liancui; Xue, Bing; He, Shengjie
Abstract : A lineark -forest of an undirected graphG is a subgraph ofG whose components are paths with lengths at mostk . The lineark -arboricity ofG, denoted byl a k (G ), is the minimum number of lineark -forests needed to decomposeG . In case the lengths of paths are not restricted, we then have the linear arboricity ofG, denoted byl a (G ). In this paper, the exact value of the linear 2- and 4-arboricity of complete bipartite graphK m, n for somem andn is obtained.